About writings of violence in black African french-speaking contemporary dramatic art (1930-2005) - (:unkn) unknown (My University, 2007)
Violence comes across black african French-speaking theatrical production since its origins. It is prone to thematic and aesthetic changes which makes it evolve from one period to another. We have thus passed from confined theatres of assimilated violence where the form was a constraint to an outburst of writings dealing with violence in contemporary works. Violence appears in the plays of William Ponty (1930) under the form of cultural conflict drawn from African customs. Turned into political violence, it embarks the dramaturgic categories during the Seventies in the confrontation of the colonizer against the colonised. With the theatre of the 1980's, violence, still political, takes however another form marked by an attempt to disrupt with classical theatrical canons. Associating the burlesque with tragedy, bypassing the French language, establishing a dialogue between tradition and modernity through an endogenous writing are as many realities characterizing the expression of conflicts about disillusionnement. In most of the plays following the1990's, on the other hand, the conflicts take on a plural image which convenes the world through distinctive modes of expression. It results in a hybrid writing in which violence is voiced out through the dislocation of the dramatic categories and of the meaning that emerges out of it. From this scriptural dynamics of violence arises a displacement of the theatrical stakes in so far as African dramas today get rid of the nationalist inclinations to endorse the world's realities. Thus the opening of contemporary theatres to the world creates a variety of forms whose complexity calls into question the concept of Africanity.
Keywords: African Research